A knowledge creation approach to environmental education in early childhood : creating a community of learners : this thesis is submitted in part fulfilment of the requirements for the Doctor of Education, Massey University - Prince, Cynthia Margaret (Massey University, 2006)
The study investigated the creation of a community of learners to integrate environmental education into early childhood curriculum. Two centres were used for the study (one kindergarten, one childcare centre). The participants were four kindergarten teachers, eight childcare staff, along with five focus group parents and six focus children from each centre. The qualitative research was conducted in two phases over one year. In phase one a case study approach was employed to allow teachers to gain confidence in the research process. During this time a two week environmental education integrated curriculum was implemented at both centres. At the conclusion of phase one a nascent community of learners was emerging. After a transition stage when the research was shared with the researcher, the teachers at both centres made the decision to lead the research in phase two using a participatory action research approach. This resulted in a growth in professional knowledge of research processes. The teachers aimed to collaboratively create a community of learners with the parents by valuing their involvement, social capital and funds of knowledge. A project approach to environmental education based on children’s environmental interests, the emergent curriculum, and the use of documentation was implemented at both centres. A conceptual artefact in the form of a community of learners was created. Bereiter’s knowledge creation metaphor and the sociological concepts of parental social capital and funds of knowledge guided the data analysis. Environmental knowledge creation by all participants in the community of learners was a significant finding. The research process resulted in all the participants (teachers, children and parents) creating their own environmental knowledge and gaining a heightened awareness of environmental education in early childhood curriculum.
Keywords: Early childhood; Community of learners; Knowledge creation; Environmental education; Participatory action research; 330110 Early childhood education